2004
DOI: 10.1126/science.1103966
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Defends Cells Against Invading Group A Streptococcus

Abstract: We found that the autophagic machinery could effectively eliminate pathogenic group A Streptococcus (GAS) within nonphagocytic cells. After escaping from endosomes into the cytoplasm, GAS became enveloped by autophagosome-like compartments and were killed upon fusion of these compartments with lysosomes. In autophagy-deficient Atg5-/- cells, GAS survived, multiplied, and were released from the cells. Thus, the autophagic machinery can act as an innate defense system against invading pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
931
1
9

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,037 publications
(961 citation statements)
references
References 18 publications
20
931
1
9
Order By: Relevance
“…[44][45][46] Autophagy has an important role in physiological and pathological processes, such as degradation of cytoplasmic components, cellular response to nutrient starvation and apoptosis. 47,48 Moreover, autophagy is also relevant in innate 49,50 and adaptive immunity. 51,52 Atg16l in conjunction with an Atg12-Atg5 conjugate, has a crucial role in the elongation of isolation membranes and the initial step of autophagosome formation, 53 and it is essential in the targeting and destruction of pathogens 49 as well as in foreign (microbial) antigen processing and presentation 52 protecting against viruses, bacteria and other pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46] Autophagy has an important role in physiological and pathological processes, such as degradation of cytoplasmic components, cellular response to nutrient starvation and apoptosis. 47,48 Moreover, autophagy is also relevant in innate 49,50 and adaptive immunity. 51,52 Atg16l in conjunction with an Atg12-Atg5 conjugate, has a crucial role in the elongation of isolation membranes and the initial step of autophagosome formation, 53 and it is essential in the targeting and destruction of pathogens 49 as well as in foreign (microbial) antigen processing and presentation 52 protecting against viruses, bacteria and other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 Moreover, autophagy is also relevant in innate 49,50 and adaptive immunity. 51,52 Atg16l in conjunction with an Atg12-Atg5 conjugate, has a crucial role in the elongation of isolation membranes and the initial step of autophagosome formation, 53 and it is essential in the targeting and destruction of pathogens 49 as well as in foreign (microbial) antigen processing and presentation 52 protecting against viruses, bacteria and other pathogens. The functional role of the ATG16L1 T300A amino-acid substitution (polar proline to nonpolar alanine) is not yet clear, but it lies at the highly evolutionary conserved position 300 in the N terminus of the WD-repeat domain in ATG16L1 and, therefore, may affect protein interactions with other components of the autophagosome.…”
Section: Discussionmentioning
confidence: 99%
“…Nakagawa and Yoshimori's group showed that group A Streptococci (GAS), upon escaping from endosomes into the cytosol by a streptolysin O-mediated process, are immediately and specifically sequestered by autophagosome-like structures. 28 These GAS-containing structures are eventually fused with lysosomes for degradation. The formation of these structures is Atg5-dependent, and in Atg5 À/À embryonic fibroblasts and embryonic fibroblasts, degradation of GAS is significantly reduced, suggesting that this autophagy-like process is indeed bactericidal.…”
Section: Degradation Of Invading Bacteriamentioning
confidence: 99%
“…The breakdown of damaged organelles and proteins via autophagy leads to the recycling of nutrients and sustains cellular energy levels. In addition, autophagy targets various intracellular pathogens such as Mycobacterium tuberculosis [1], Salmonella enterica serovar Typhimurium [2], Legionella pneumophila [3], Streptococcus pyogenes [4], and Burkholderia cenocepacia [5]. This bacteria-specific autophagic process, designated xenophagy, promotes bacterial clearance and prevents cellular escape.…”
Section: Introductionmentioning
confidence: 99%